1996
DOI: 10.1002/ana.410400209
|View full text |Cite
|
Sign up to set email alerts
|

Campylobacter jejuni infections and anti‐GM1 antibodies in guillain‐barré syndrome

Abstract: The group of patients with Guillain-Barr'e syndrome (GBS) is very heterogenous with regard to antecedent infections, immunological parameters, clinical manifestations, and response to treatment. In this study, the presumed pathogenic factors anti-GM1 antibodies and Campylobacter jejuni infections were related to the clinical characteristics. Serum from 154 patients with GBS, 63 patients with other neurological diseases (OND), and 50 normal controls (NC) were tested for the presence of antibodies against GM1 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
197
0
5

Year Published

1997
1997
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 301 publications
(215 citation statements)
references
References 35 publications
(16 reference statements)
6
197
0
5
Order By: Relevance
“…It was hypothesized that different sub-types of anti-ganglioside antibodies are associated with different GBS subtypes (35). Anti-GM1 antibodies are commonly associated with a pure motor variant of GBS (36), and GQ1b may be a target antigen responsible for patients with MFS (37). A study reported that anti-ganglioside antibodies are able to inhibit axon regeneration through neuronal gangliosides independent of endogenous regeneration inhibitors (38).…”
Section: Discussionmentioning
confidence: 99%
“…It was hypothesized that different sub-types of anti-ganglioside antibodies are associated with different GBS subtypes (35). Anti-GM1 antibodies are commonly associated with a pure motor variant of GBS (36), and GQ1b may be a target antigen responsible for patients with MFS (37). A study reported that anti-ganglioside antibodies are able to inhibit axon regeneration through neuronal gangliosides independent of endogenous regeneration inhibitors (38).…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical studies indicate that anti-ganglioside Abs are associated with poor/incomplete recovery (Ilyas et al, 1992;Gregson et al, 1993;Simone et al, 1993;Yuki et al, 1993;Jacobs et al, 1996;Bech et al, 1997;Kuwabara et al, 1998a,b;Carpo et al, 1999;Press et al, 2001;Annunziata et al, 2003;Koga et al, 2003;Kaida et al, 2007). The patients with incomplete recovery almost always have some degree of failure of nerve repair/axon regeneration and target reinnervation (Brown and Feasby, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…The full spectrum of anti-ganglioside Ab-mediated pathobiologic effects and associated mechanisms remain to be defined. Several studies suggest that some GBS patients with anti-ganglioside Abs directed against GM1, GD1a, or ganglioside complexes have poor prognosis and/or incomplete recovery (Ilyas et al, 1992;Gregson et al, 1993;Simone et al, 1993;Yuki et al, 1993;Jacobs et al, 1996;Bech et al, 1997;Kuwabara et al, 1998a,b;Carpo et al, 1999;Press et al, 2001;Annunziata et al, 2003;Koga et al, 2003;Kaida et al, 2007). We recently demonstrated that experimental monoclonal and GBS patient-derived anti-ganglioside Abs can inhibit regeneration of injured axons in an animal model (Lehmann et al, 2007;Lopez et al, 2010), suggesting that Ab-mediated inhibition of nerve repair is one mechanism of delayed recovery.…”
Section: Introductionmentioning
confidence: 97%
“…Her neurological symptoms started 1 week later: she consulted her general practitioner because of generalised muscle pain, a rigid neck and a painfully rigid left hand. Routine blood investigations at that moment only showed a slight increase in leucocytes (10 690/mm 3 , reference value 4000-10 000/mm 3 ) and SGPT (28 U/l, reference value o22 U/l). A symptomatic treatment consisting of paracetamol q6h and an intramuscular injection with diclofenac was prescribed.…”
Section: Case Reportmentioning
confidence: 90%
“…3 Acute-phase pretreatment serum contained high titres of anti-GM1 IgG (1:6400) and IgM (1:400) antibodies, which were decreased in a serum sample obtained at 6 months: IgG (1:200) and absent IgM. Both samples were negative for IgG and IgM antibodies to GM2, GM3, GD1a, GD1b, GD2, GD3, GT1a, GT1b and GQ1b.…”
Section: Case Reportmentioning
confidence: 90%